The Impact of Relational and Organizational–Environmental Aspects in Hospital Blood Collection: Clinical and Health Indications and New Training Needs - Iudici, Antonio; De Donà, Donata; Faccio, Elena; Neri, Jessica; Rocelli, Michele; Turchi, Gian Piero (Frontiers in Public Health, 2021)
This study deals with people who underwent a blood test and consequently suffered a fainting episode in the past. This phenomenon affects many people and if not adequately dealt with, it can lead to a perception of the blood test as a serious and traumatic event, which could limit its use as a preventive diagnostic tool. These experiences have been explored by research mainly on the basis of the physiological mechanisms involved in fainting, with a few studies considering the actual lived experience related to the blood test. This study explored how this experience is lived and managed, capturing aspects that could facilitate blood tests and the procedures associated with them, thus it focused on people with vasovagal syncope and was articulated through the semi-structured interview methodology. Among the significant results is the importance of the relational aspects implemented by health staff, the differing organisation of the blood test procedure, the need to make the hospital environment less aseptic and more humanistic, effective actions to counter the anxieties relating to the administration of the blood test and the importance of including the blood test with an inter-disciplinarity perspective.